Siasat Komunikasi Pemandu Lagu Terhadap Pelanggannya di Karaoke Widari - Elsa Septiana Pertiwi; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Karaoke guide is one of the jobs that is currently occupied by a number of parties, this profession is related to services and music, especially in the world of singing. Because it is considered that having a job as a song guide is not difficult, has sound capital, and an attractive appearance. They are only required to have an attractive appearance, in accordance with the wishes of the general customer, which is beautiful and sexy because most of the customers are men. This profession, not only accompanies guests singing, but is also responsible for customer satisfaction. The more guests are satisfied with the service, the greater the tip that will be received by the song guide. Social construction and society's view of karaoke workers. The aim of this research is to find out the communication strategy of the song guides to their customers at karoke widari. The research uses a phenomenological method that explains the individual's experience when experiencing phenomena in real life or everyday life. The research was conducted in Karoke Widari, Semarang City by using purposive sampling as many as 5 informants. The results of the study revealed that the informant who got a job as a karaoke guide got an offer from his friend. An artist, especially a karaoke song guide, of course must have a warm, friendly nature to guests because that is the initial capital of a song guide who certainly wants what is displayed to get appreciation from song guide service users. Working as a song guide is not easy, especially for those who already have families and some are still in college, of course, they have a double role. The song guides in this study were able to play three different roles in their life processes, such as from the way they look, the way they talk, the way they interact, their activities and routines are carried out in two different roles, and are able to carry out these roles simultaneously, this is proven. with the roles they play, namely the front stage and the back stage, where there is diversity that emerges